The Resolution of the Problems Encountered in the Contemporary Church Using the First Patristic Letter as a Template - Vadana, Roby (Asian Horizons, 2024)
As the first letter among the Apostolic Fathers in the study of Patrology, The First Letter of Clement to the Corinthians stands as a pivotal document. Following internal divisions and disputes within the Corinthian Church, Clement, writing from the Church of Rome as the successor of St. Peter, composed this letter as an appeal to the Corinthians to address the conflicts and restore peace and unity in their community. Clement emphasizes the importance of apostolic succession and urges everyone to honour and obey the legitimate authority within the Church. He points out that the dispute in the Church stems from strife and jealousy, and calls on the Corinthians to repent for the disorder they have caused. Clement encourages them to adopt humility and obedience following the example set by Christ and the Apostles. Today, more than ever, Clement’s letter remains deeply relevant as the contemporary Church faces growing divisions and disputes. It serves as a reminder to the Church today of her responsibility to stand alongside every local Church, diocese, community, and member, just as the Roman church stood with the Corinthians. The letter calls for the Church to seek unity and resolution through mutual support and correction, rather than through condemnation and alienation. Clement cautions that hatred, envy, and jealousy are contrary to the Christian faith and will ultimately harm the Church. He exhorts the faithful to pursue unity and peace, virtues that can only be achieved through repentance, humility and obedience. The Church today must rediscover the warmth of the early Christian community to experience the genuine spirit of love and unity.